Cardiac computed tomography assessment of the near term impact of percutaneous ventricular restoration therapy (parachute®) on mitral valve geometry. Issue 2 (3rd November 2015) - Tam, Chor Cheung; Fares, Anas; Alaiti, Amer; Shaikh, Kashif; Ince, Hüseyin; Erglis, Andrejs; Bezerra, Hiram G.; Abraham, William T.; Costa, Marco A.; Attizzani, Guilherme F.
Abstract : Objectives: The aim of current study is to assess the near term impact of percutaneous ventricular restoration therapy (PVR), Parachute ® on mitral valve (MV) geometry by cardiac computed tomography (CCT). Background: Recent data demonstrates the feasibility of PVR for treatment of post anterior myocardial infarction (MI) heart failure. Little is known, however, about the interaction of the device and left ventricular structures, particularly the MV apparatus. Methods: This is a retrospective Core Laboratory analysis of Parachute Trials' CCT data. Patients with paired (before and after Parachute implant) CCT acquisitions were included into analysis. MV geometric parameters were measured. Results: Thirty‐three patients were included in the analysis. The mean time of follow‐up CCT post procedure was 188 ± 52 days. There were significant reduction in tenting height (A1P1: −1.70 ± 1.89 mm, −17.40 ± 20.20%; A2P2: −1.43 ± 1.89 mm, −12.10 ± 15.00%; A3P3: −1.54 ± 1.58 mm, −15.50 ± 15.20%, P < 0.001), tenting volume (−0.93 ± 0.60 mm3, −22.00 ± 11.40%, P < 0.001), systolic interpapillary muscle distance (−2.22 ± 2.11 mm, −7.51 ± 7.23%, P < 0.001) and diastolic interpapillary muscle distance (−3.14 ± 2.20 mm, −8.46 ± 5.73%, P < 0.001) post PVR. Conclusions: In post anterior MI heart failure patients, PVR has favorable near term impact on MV geometry as assessed by CCT. © 2015 Wiley Periodicals, Inc.